Preliminary survey on potential toxic heavy metal content and distribution in soils of Ranau District, Sabah, Malaysia - Sahibin Abdul Rahim (Universiti Kebangsaan Malaysia, 1996)
A preliminary study on the concentration and distribution of heavy metals (Cd, Co, Cr, Cu, Ni, Pb and Zn) was carried out for the whole of Ranau District. Topsoil samples (0-15 cm depth) were collected randomly in accordance with the distribution of soil associations in the area. It was found that only three of the heavy metals (Ni, Cr, and Cu) were present above the threshold of toxicity level, whilst the others were below this level. These higher levels of heavy metal concentration were most likely associated with the mining activities in the headwater of the study area and also to the occurrence of serpentinite parent material. The area affected is confined only to the northern part of the study area.